Unlocking Potential: Growth vs. Fixed Mindset Explained - Indrani Lahiri (8445576) (2025)
Welcome to our YouTube channel dedicated to building resilience in children! Our goal is to provide parents, educators, and caregivers with practical tools and strategies to help children develop the skills they need to bounce back from challenges and adversity. Through a combination of expert interviews, real-life stories, and practical tips, we aim to empower parents and caregivers with the knowledge they need to help children build resilience and thrive. Our team of experts includes psychologists, educators, and child development specialists, who bring years of experience and research to their advice and insights. We believe that every child deserves the opportunity to develop resilience and thrive, and we are committed to providing the tools and resources parents and caregivers need to help children reach their full potential. So if you're looking for practical advice, expert insights, and inspiring stories on building resilience in children, you've come to the right place! Links Facebook<a href="https://www.youtube.com/redirect?event=channel_description&redir_token=QUFFLUhqbVVHaW1fY25xS1dvTlp5eU9Oc01zM25uTDNqd3xBQ3Jtc0trdGRrLTNmRWFBZHB4bm1BS0wtZlk2VGF0WTVjUXpnZ0pYYTNBRzFYRno0NV9FbDZBbmpMcGFjdG9HMEk3U1VFaEpjOG41OWZuWjBHUENPVkt3Sk9RRDNZWmZvRl92b1d1ZlhyTkpCYndaUVlfSUlERQ&q=https://www.facebook.com/childrenstoriesintimesofcorona" rel="nofollow" target="_blank">facebook.com/childrenstoriesintimesofcorona Instagram<a href="https://www.youtube.com/redirect?event=channel_description&redir_token=QUFFLUhqbVZLWHUySmtmamJtbXRWYnFOUzNMZHVpV3Jxd3xBQ3Jtc0tta3ZnM2xtenlaNTNiMVdpQUdFa1pva0E1bGMzN1hfb1ctU01VMFdiZkp5bW9MOVVmakVjdjR1Sk9nS0NRWXBCVWJZclhQTWhYY3Z2cXBVT1hoVXByVUZvTlExZGRubGxScUhiTUxhNzRaTEo0dFhQTQ&q=https://www.instagram.com/bric_2022/" rel="nofollow" target="_blank">instagram.com/bric_2022 Website<a href="https://www.youtube.com/redirect?event=channel_description&redir_token=QUFFLUhqbmt3N0oteU5ieUg1THkwdnRsOTFxM0hjZzI5Z3xBQ3Jtc0ttOVNmMVJjczlRcXI0SFFFaEhReS1waDkyN3VISFBVOVdBUm9PVDQ5MDg5OGVrclVCcGtPa1p5VllNSm1MS3FacXR2b09YRnlQS0xlMTNwb29uenVkcDlmbGpBVmpQYTNoaVZJY1NiNHJybkRDWi00RQ&q=https://www.bric2022.com" rel="nofollow" target="_blank">bric2022.com Twitter<a href="https://www.youtube.com/redirect?event=channel_description&redir_token=QUFFLUhqbjJzTjU0eDdCbXVDcGdjVVVQTFZISHppMldUd3xBQ3Jtc0tudUsyVGVmaGhtTll1bEw2WGx3ajBwb0wwUXo5ZVMyVU91VUtWZW50N1cyZjF5TU9FWTd4RVdmWDd3UkRHRDRXWWt6SGwtVXlYdS0yMkRrZ1lreFJ1Y0x2QmFvd2YteFRUNWFtUV9GMjBBX2RxQURuOA&q=https://twitter.com/bric2022" rel="nofollow" target="_blank">twitter.com/bric2022 Issuu<a href="https://www.youtube.com/redirect?event=channel_description&redir_token=QUFFLUhqbGRhcTk0WGtkMXdSMmhSR0tWMzVBQzRRdU5Xd3xBQ3Jtc0trdFIxakZaWDFSbk5Rdk41YlNqT2VPUVVQbmdPUGJwOHVmV0JaemJ1Z2d1clg1a3h0b1VFNG1pU1ZfLWFqaUhISHlwWVp4LVlUV0d3a0pMN2tvUVhrbnFaa3NmeG9LR1V6VDJBdGRybElZLS02NUUwcw&q=https://issuu.com/bric22" rel="nofollow" target="_blank">issuu.com/bric22 Channel details www.youtube.com/@bric22 1.54K subscribers 249 videos 42,628 views